COLLECTIVISM, GENDER, REWARD AND PUNISHMENT ON FINANCIAL STATEMENT FRAUD - Nirma Mufaidah Dwi Ajeng Suhermanto; Sarwenda Biduri; Nurasik Nurasik (International Journal of Business, Law and Political Science, 2024)
Collectivism, Gender, Reward and Punishment on Financial Statement Fraud. Financial statement fraud is a deliberate omission in presenting data either in the form of disclosures or amounts in financial statements that are designed to cause losses to users of financial statements. This study aims to determine: The Effect of Collectivism on Financial Statement Fraud, The Effect of Gender on Financial Statement Fraud, The Effect of Reward on Financial Statement Fraud, The Effect of Punishment on Financial Statement Fraud. The data analysis technique in this study used multiple linear regression with the help of SPSS (Statistical Package for Social Science). The results showed that there was no effect of Collectivism on Financial Statement Fraud, there was no effect of Gender on Financial Statement Fraud, there was an effect of Reward on Financial Statement Fraud, there was an effect of Punishment on Financial Statement Fraud. These results are expected to provide recommendations for students in evaluating themselves regarding the importance of ethics and the character of accounting students in reducing the intention to commit fraudulent behavior.